2019
DOI: 10.1016/j.psychres.2018.11.046
|View full text |Cite
|
Sign up to set email alerts
|

Adult report of childhood imaginary companions and adversity relates to concurrent prodromal psychosis symptoms

Abstract: Highlights Childhood imaginary friend report predicted adult prodromal hallucination symptoms. Childhood imaginary friend report did not predict other adult prodromal symptoms. Childhood adversity report predicted all types of adult prodromal symptoms. Childhood adversity mediated imaginary friend prodromal hallucination symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…These findings partly explain previous studies suggesting the relation between having childhood IC and reporting hallucination-like experiences in adults (Davis et al, 2019;Fernyhough et al, 2007;Fernyhough et al, 2019), as is shown in this study that having IC in childhood predispose adolescents to higher schizotypy scores. This effect was seen among all IC types (invisible, personified object, and impersonation) and without gender moderation.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These findings partly explain previous studies suggesting the relation between having childhood IC and reporting hallucination-like experiences in adults (Davis et al, 2019;Fernyhough et al, 2007;Fernyhough et al, 2019), as is shown in this study that having IC in childhood predispose adolescents to higher schizotypy scores. This effect was seen among all IC types (invisible, personified object, and impersonation) and without gender moderation.…”
Section: Discussionsupporting
confidence: 91%
“…To date, no studies have directly investigated the relation between having childhood ICs and scoring higher on schizotypy inventories among adolescents. However, similar studies demonstrated the relation between having ICs in childhood and reporting prodromal psychosis symptoms in adults (Davis et al, 2019). This study aimed to find, if any, differences between the two groups of adolescents (with childhood IC and without childhood IC) in scores of schizotypy dimensions.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…This study, like Davis et al (2018) was based only on retrospective parent report which comes with some inherent issues. The retrospective nature does not take into account that ICs can be forgotten by parents ( Davis et al, 2019 ) and the parent report means that the study loses the child’s voice along with ecological validity. One issue specific to this study was that parents completed the questionnaire more quickly than anticipated.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation for these opposing findings is the recruitment of samples from outpatient clinics and without control groups in earlier studies (Taylor, 1999). Indeed, prevalence rates of children having ICs, 13 to 65 %, emphasize the normality of this phenomenon (Davis et al, 2019;Pearson, 1998;Svendsen, 1934;Taylor et al, 2004). Moreover, research into personality characteristics and behavioral correlates of IC play demonstrated a range of positive attributes.…”
Section: P a G E 1 6 0 P A G E 1 6mentioning
confidence: 99%